Influence of temperature on the development of Dirphia araucariae - Borges, Jácomo Divino (Pesquisa Agropecuaria Brasileira, 2014)
The influence of temperature on the development of Dirphia araucariae Jones, 1908 (Lepidoptera: Attacidae) at 20°C and 25°C was studied. The mean incubation period was 26.17 and 24.67 days, respectively. The larval stage presented six instars and lasted for 62.80 and 65.39 days for males and females, respectively, at 20°C. At 25°C, the caterpillars presented six and seven instars, and the mean duration of this stage was, respectively, 52.78 and 54.54 days for males and females in the six-instar caterpillars, and 66.67 and 63.82 days in the seven-instar ones. The mean duration of the pre-pupal stage, for males and females was 6.31 and 6.11 days at 20°C, and 4.63 and 5.04 days at 25°C after the caterpillars have passed through six instars, and 4.67 and 4.64 days at 25°C in the seven-instar caterpillars. At 20°C, the pupal stage lasted for 52.51 and 51.13 days for males and females, respectively. The duration of this stage at 25°C was not determined, because a mortality of 100% of pupae occurred at this stage, at this temperature. The sex ratio (♂ : ♀) at the pupal stage was 1:0.93 at 20°C, and 1:1.17 at 25°C.